2023
DOI: 10.1186/s12967-023-04575-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dynamic interplay between cancer stem cells and the tumor microenvironment: implications for novel therapeutic strategies

Yan-Ruide Li,
Ying Fang,
Zibai Lyu
et al.

Abstract: Cancer stem cells (CSCs) have emerged as key contributors to tumor initiation, growth, and metastasis. In addition, CSCs play a significant role in inducing immune evasion, thereby compromising the effectiveness of cancer treatments. The reciprocal communication between CSCs and the tumor microenvironment (TME) is observed, with the TME providing a supportive niche for CSC survival and self-renewal, while CSCs, in turn, influence the polarization and persistence of the TME, promoting an immunosuppressive state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 321 publications
0
14
0
Order By: Relevance
“…CSCs are the main culprits for the heterogeneity of cancer as they are responsible for cancer initiation, invasive front formation, and drug resistance. It is suggested that the mechanical forces induced by the dense ECM might activate the autophagy and Hippo pathways to promote CSC proliferation and stemness[ 56 , 57 ]. Thus, an alternative explanation for the generation of heterogenous CSC populations (except for their intrinsic differences) might be that the heterogenous TME exerts differential mechanical forces on these cells[ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSCs are the main culprits for the heterogeneity of cancer as they are responsible for cancer initiation, invasive front formation, and drug resistance. It is suggested that the mechanical forces induced by the dense ECM might activate the autophagy and Hippo pathways to promote CSC proliferation and stemness[ 56 , 57 ]. Thus, an alternative explanation for the generation of heterogenous CSC populations (except for their intrinsic differences) might be that the heterogenous TME exerts differential mechanical forces on these cells[ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…To understand this relationship between cancer progression and CSCs, we should first recognise the nature of CSCs. Thus, the most relevant differentiating and characterising features of normal stem cells and CSCs are included in Table 1 [2][3][4]6,9,10,13,[23][24][25][26][27][28][29][30]. Notch, Oct4, Sox1: specific genes for all stem cells; ALDH1: aldehyde dehydrogenase 1; CD24: a small surface protein responsible for cell-extracellular matrix (ECM) and cell-cell interactions; CD34: a transmembrane glycoprotein expressed on early lymphohematopoietic stem cells, progenitor cells, and endothelial cells; CD44: a multifunctional glycoprotein responsible for cell adhesion, signalling, proliferation, migration, haematopoiesis, and lymphocyte activation; CD90: a glycophosphatidylinositol (GPI) anchored conserved cell surface protein; CD133: also known as prominin-1, a transmembrane cell surface glycoprotein commonly utilised as a hematopoietic stem cell marker; CSCs: cancer stem cells; DNA: deoxyribonucleic acid; EpCAM: epithelial cell adhesion molecule; ESA: epithelial-specific antigen; IL-4: interleukin 4; * It means that Early-stage CSCs and Late-stage CSCs are subpopulations of CSCs.…”
Section: Cancer Stem Cells: Origin and Detailed Characteristicsmentioning
confidence: 99%
“…The stem cell niche refers to the space in which stem cells are kept ready for the self-renewal, cell division, and differentiation necessary to maintain tissue homeostasis [2,27,31]. The specific features of niches for CSCs are disruption of the immune system and accumulation of malignant cells [2,24,29,32]. In this context, it is important to take into account that chronic inflammation is a natural driver in cancer-triggering niches.…”
Section: The Importance Of the Tissue-specific Microenvironment For T...mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, FAP is upregulated at sites of tissue remodeling, including chronic arthritis, solid tumors, and fibrotic hearts [ 8 ]. While FAP has been recognized as a potential diagnostic or therapeutic cancer target for decades [ 9 , 10 ], its role in cardiac fibrosis remains unclear. Aghajanian et al, using a novel CAR-T cell therapy against FAP, observed a significant reduction in cardiac fibrosis and restoration of function after injury in mice [ 11 ].…”
Section: Introductionmentioning
confidence: 99%